Enhancing Buck-Boost Converter Efficiency and Dynamic Responses with Sliding Mode Control Technique - Salah Hilo Mohammed Al-Attwani; Mustafa Teke; Ethar Sulaiman Yaseen Yaseen; Enes Bektaş; Nurettin Gökşenli (Journal of Techniques)
DC-DC converters are an important class of power electronics due to their wide use in various applications as sources of efficient power supplies. They step down or step up the applied voltage so that it is always either lower or higher than the supplied voltage. This is crucial in power delivery and portable systems, especially in battery-operated systems. The purpose of the paper is to investigate how the efficiency of Buck-Boost converters improves by using sliding mode control when operating under different conditions. The work aims to develop a control strategy that increases the efficiency and reliability of Buck-Boost converters, employed in a myriad of power electronics applications. The research focuses on a sliding mode control approach to overcome the challenges of nonlinear dynamics and susceptibility to external disturbances. The methodology involves studying the behavior of the converter under different conditions such as changes in loads, input voltage variations, and reference voltage changes. The study uses theoretical modeling and simulation to evaluate the concept of sliding mode in addressing the challenges for improved efficiency. Such investigations show how sliding mode control improves efficiency. SMC approach reduces the response time by 5%, improves efficiency by 3%, and enhances overall stability under fluctuating conditions. The use of sliding mode control enhances the converters against disturbances and provides an efficient voltage regulator. The research is useful to the field as it offers more insights into the control strategy that significantly improves the performance of converters concerning efficiency and stabilization.